Pengaruh Ekstrak Jahe Merah (Zingiber Officinale.) Terhadap Pertumbuhan Bakteri Shigella Dysentriae - NI KADEK SINTA DWI CHRISMASYANTI; KADEK DENIK SUASTINI; NI LUH SURAS AMOURA CAWIS; NI WAYAN SUCINDRA DEWI (HANG TUAH MEDICAL JOURNAL, 2021)
Abstract Diarrheal disease in Indonesia is still a high health problem for its morbidity and mortality rates. Diarrhea is still a cause of death in children under 5 years, amounting to 25.2%. Diarrhea morbidity in Indonesia during 2015 reached 6,897,463 and diarrhea that had been handled reached 2,544,084 or as much as 36.9%. The most important and most common cause of diarrhea in developing countries is Shigella, especially Shigella dysentriae and Shigella boydi which causes diarrhea with dysentery. One natural ingredient that has the potential to treat Shigella Dysentriae bacteria is ginger (Zingiber officinale). The ginger plant itself is very abundant in Indonesia. The antibacterial effect against Shigella dysenteriae is due to the active ingredient in ginger, namely gingerol, which inhibits the antibacterial activity of phenolics, flavonoids with an inhibitory mechanism by denaturing bacterial cell wall proteins.